The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1590/s0006-87051993000200006
|View full text |Cite
|
Sign up to set email alerts
|

Amarelecimento do arroz-de-sequeiro sob condições de encharcamento em solo de baixa fertilidade

Abstract: Foi realizado um experimento em vasos visando reproduzir sintomas de amarelecimento foliar observados em arroz-de-sequeiro em condições de campo, em Assis (SP), e estudar suas possíveis causas nutricionais. Os tratamentos constituíram-se de areia quartzosa retirada da camada de 0-20 cm, submetida a dois manejos (solo original e solo calcariado e cultivado), dois tipos de irrigação (padrão e excessiva) e quatro cultivares de arroz (IAC-25, IAC-47, Araguaia e Rio Paranaíba). Foram avaliados os sintomas de amarel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

1998
1998
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
(10 reference statements)
0
3
0
3
Order By: Relevance
“…(Duarte et al, 1993), o qual não foi mencionado no trabalho de Ferreira et al (1986). Outro aspecto é que o comportamento da produção de massa verde da parte aérea do presente trabalho não coincide necessariamente com a produção de grãos.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…(Duarte et al, 1993), o qual não foi mencionado no trabalho de Ferreira et al (1986). Outro aspecto é que o comportamento da produção de massa verde da parte aérea do presente trabalho não coincide necessariamente com a produção de grãos.…”
Section: Resultsunclassified
“…Em arroz, constatou-se que a razão C/CV aumenta com o encharcamento do solo (Duarte et al, 1993). O fato de o 'IAC 165' não ter apresentado um aumento da produção de massa verde da parte aérea e ter havido uma diminuição na razão C/CV em doses maiores do que 2 t.ha -1 de calcário dolomítico, são indicativos de sua menor resposta à calagem nessa condição de encharcamento temporário do arroz-de-sequeiro.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…A study of upland rice grown under excessive irrigation reported an increase in cortical thickness (Duarte et al 1993). For different sugar cane cultivars growing in different soil conditions (dry, irrigated, and soggy), differences in root anatomy were reported, mainly related to the thickness of cortex and vascular cylinder (Venkatraman and Thomas 1922).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in dry environments a reduced number of cortical layers are formed, suggesting that a small distance between the substract and the stele would help the water absorption in these conditions (Fahn 1982). Moreover, when growing in dump soil, the rice roots form a thick cortex (Duarte et al 1993), and Venkatraman and Thomas (1922) noticed that, for sugar cane cultivars, the relation between the cortex and vascular cylinder thickening was bigger when the plants grow in soaked soils.…”
Section: Discussionmentioning
confidence: 99%